2015
DOI: 10.2139/ssrn.2635616
|View full text |Cite
|
Sign up to set email alerts
|

Political Identity and Trust

Abstract: We explore how political identity a¤ects trust. Using an incentivized experimental survey conducted on a representative sample of the U.S. population, we vary information about partners'partisan identity to elicit trust behavior, beliefs about trustworthiness, and actual reciprocation. By eliciting beliefs, we are able to assess whether di¤erences in trust rates are due to stereotyping or a "taste for discrimination." By measuring actual trustworthiness, we are able to determine whether beliefs are statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In addition to controlling for SES, we controlled for other socio-demographic and ideological factors likely to affect trust, such as marital status, religion, and political orientation. In this regard, previous research has found that individuals’ political ideology can modulate their trust ( Hernandez and Minor, 2015 ) and that propensity to trust others is greater among married men and women ( Lindström, 2012 ) and non-religious people ( Berggren and Bjørnskov, 2011 ). In addition, given that the increase in unemployment is one of the most important consequences of the economic crisis in Spain ( López-Jiménez and Renes, 2011 ), we also included this variable in the regression equations.…”
Section: Studymentioning
confidence: 99%
“…In addition to controlling for SES, we controlled for other socio-demographic and ideological factors likely to affect trust, such as marital status, religion, and political orientation. In this regard, previous research has found that individuals’ political ideology can modulate their trust ( Hernandez and Minor, 2015 ) and that propensity to trust others is greater among married men and women ( Lindström, 2012 ) and non-religious people ( Berggren and Bjørnskov, 2011 ). In addition, given that the increase in unemployment is one of the most important consequences of the economic crisis in Spain ( López-Jiménez and Renes, 2011 ), we also included this variable in the regression equations.…”
Section: Studymentioning
confidence: 99%
“…Exploring these effects is a topic for future research. such as those of Hernandez and Minor (2015) indicate that the increase in trust resulting from the knowledge that one's associate shares one's political affiliation is very much smaller than the decrease in trust resulting from the knowledge that one's associate has a different political affiliation. In this case, our results correspond to a negative externality: the promotion of a partisan culture increases trade costs.…”
Section: Discussionmentioning
confidence: 99%
“…The electorate is now highly partisan (Brewer, 2005;Iyengar and Westwood, 2015;Perez-Truglia and Cruces, 2017), and inter-city differences in party strength are reinforced by pressure to conform to the local majority (Perez-Truglia, 2018). Experimental results indicate that interpersonal trust between Republicans and Democrats is much lower than trust within each group (Hernandez and Minor, 2015;Carlin and Love, 2018). In this environment, it is possible that arbitrage between cities becomes more difficult when one of the producers / retailers is from a strongly Republican city while the other is from a strongly Democrat city, or when one city is culturally "southern" and the other culturally "northern".…”
Section: Literature Reviewmentioning
confidence: 95%
“…Existing articles examine the different factors that might influence confidence in institutions. Some examine the link between democracy and trust (see Anderson and Guillory 1997), while others discuss the trust among individuals and link it to partisan identities (see Hernandez and Minor 2015). Given the recentness of the subject, only a handful of articles mention the link that might exist between social identity 13 and confidence in institutions during or post Arab Spring.…”
Section: Trust Institutions and Identitymentioning
confidence: 99%